Impact of Different Tidal Volume Levels at Low Mechanical Power on Ventilator-Induced Lung Injury in Rats - Moraes, Lillian; Silva, Pedro L.; Thompson, Alessandra; Santos, Cintia L.; Santos, Raquel S.; Fernandes, Marcos V. S.; Morales, Marcelo M.; Martins, Vanessa; Capelozzi, Vera L.; de Abreu, Marcelo G.; Pelosi, Paolo; Rocco, Patricia R. M. (Frontiers in Physiology, 2018)
Tidal volume (VT) has been considered the main determinant of ventilator-induced lung injury (VILI). Recently, experimental studies have suggested that mechanical power transferred from the ventilator to the lungs is the promoter of VILI. We hypothesized that, as long as mechanical power is kept below a safe threshold, high VT should not be injurious. The present study aimed to investigate the impact of different VT levels and respiratory rates on lung function, diffuse alveolar damage (DAD), alveolar ultrastructure, and expression of genes related to inflammation (interleukin [IL]-6), alveolar stretch (amphiregulin), epithelial (club cell secretory protein [CC]16) and endothelial (intercellular adhesion molecule [ICAM]-1) cell injury, and extracellular matrix damage (syndecan-1, decorin, and metalloproteinase [MMP]-9) in experimental acute respiratory distress syndrome (ARDS) under low-power mechanical ventilation. Twenty-eight Wistar rats received Escherichia coli lipopolysaccharide intratracheally. After 24 h, 21 animals were randomly assigned to ventilation (2 hours) with low mechanical power at three different VT levels (n=7/group): 1) VT=6mL/kg and respiratory rate (RR) adjusted to normocapnia; 2) VT=13mL/kg; and 3) VT=22mL/kg. In the second and third groups, RR was adjusted to yield low mechanical power comparable to that of the first group. Mechanical power was calculated as [(ΔP,L2/Est,L)/2]×RR (ΔP,L=transpulmonary driving pressure, Est,L=static lung elastance). Seven rats were not mechanically ventilated (NV) and were used for molecular biology analysis. Mechanical power was comparable among groups, while VT gradually increased. ΔP,L and mechanical energy were higher in VT=22mL/kg than VT=6mL/kg and VT=13mL/kg (p<0.001 for both). Accordingly, DAD score increased in VT=22mL/kg compared to VT=6mL/kg and VT=13mL/kg (23[18.5–24.75] vs. 16[12–17.75] and 16[13.25–18], p<0.05, respectively). VT=22mL/kg was associated with higher IL-6, amphiregulin, CC16, MMP-9, and syndecan-1 mRNA expression and lower decorin expression than VT=6mL/kg. Multiple linear regression analyses indicated that VT was able to predict changes in IL-6 and CC16, whereas ΔP,L predicted pHa, oxygenation, amphiregulin, and syndecan-1 expression. In the model of ARDS used herein, even at low mechanical power, high VT resulted in VILI. VT control seems to be more important than RR control to mitigate VILI.